Nomenclatural clarification of Mitracarpus salzmannianus (Rubiaceae, Spermacoceae), a widespread species from South America, with notes on its conservation status - Portela, Luís Henrique Ximenes; Silva, Sabrina Barros Da; Delprete, Piero Giuseppe; Gonçalves-Oliveira, Rodrigo César; Bovini, Massimo G.; Souza, Elnatan Bezerra De (Phytotaxa, 2026)
Nomenclatural adjustments in the genus Mitracarpus proposed the combination Mitracarpus strigosus for a common South American taxon. However, this name is based on Spermacoce strigosa, a later homonym of a rejected name, which renders the combination illegitimate. In this study, we reaffirm Mitracarpus salzmannianus as the correct and legitimate name for this species, addressing long-standing nomenclatural instability by formally designating lectotypes for M. salzmannianus and M. rudis, as well as a neotype for M. discolor. We also resolve the composition of historical mixed collections that have caused confusion in the past, provide diagnostic characters to distinguish this species from its closest morphological allies, and present a geographic distribution map alongside a preliminary conservation assessment.